The Effect of Work Stress and Work Motivation on The Performance of Palopo Religious Court Employees with Integrity Zone Standards - Nur Fadhilah Safrillah; M. Risal (Yayasan Ahmar Cendekia Indonesia, 2022)
This study aims to determine the effect of work stress and motivation on the performance of employees of the Palopo Religious Court. This study uses a quantitative descriptive approach. The research population was all employees at the Palopo Religious Court, amounting to 27 people. This study uses a proportional stratified random sampling technique. Data analysis uses structural equation modeling (SEM) with the help of the Smart PLS application. The results showed that work stress did not affect employee performance by -0.098 units with a t-count value of 0.060 <1.708 or a p-value of 0.912> 0.05. Work motivation has an effect on employee performance by 5.644 > 1.708 or p-value of 0.000 < 0.05. The combined effect of work stress and work motivation on employee performance is 65%, while 35% is influenced by other variables not observed in this study.